Optimizing watchtower locations for forest fire monitoring using location models. (January 2015) - Bao, Shitai; Xiao, Ningchuan; Lai, Zehui; Zhang, Heyuan; Kim, Changjoo
Abstract: Automated forest fire monitoring systems can be constructed using forest fire watchtowers equipped with laser night vision cameras or high-definition video cameras. In order to minimize the construction cost and to maximize the monitoring coverage of forest fires, efficiently placing the watchtowers is critical. This paper examines efficient watchtower locations by integrating visibility analysis and location-allocation models. Specifically, based on the classical location set covering problem and maximum covering location problem, three optimization models are developed to satisfy three kinds of requirements of forest fire monitoring in practice: minimizing cost with full coverage, maximizing coverage with a fixed budget, and maximizing coverage while minimizing the cost. The models are tested using integer programming and a multi-objective genetic algorithm, with an application in a forest park in Guangzhou, China. The results suggest that this model-based optimization approach to watchtower location can be used to improve the efficiency of forest fire alarm systems. Highlights: Optimization models were developed to find optimal watchtower locations. Explored tradeoff between coverage and cost using abiobjective optimization model. Tested using the data from a forest part in Guangzhou, China.